Race, gender and sport : the politics of ethnic "other" girls and women - Ratna, Aarti; Samie, Samaya F. (Abingdon, Oxon ; New York, NY : Routledge, 2018)
The experiences of ethnic 'Other' females have--until recently--been widely overlooked in the study of sport. There continues to be a need to produce critical scholarship about ethnic 'Other' girls and women in sport and physical culture, in order to represent their complex, multifarious and dynamic lived realities. This international collection of critical essays provides compelling insight into the lived realities of ethnic 'Other' females in sport. Throughout the book, contributors either draw on the political consciousnesses of 'Other' feminisms, or privilege the voices of ethnic 'Other' girls and women so as to broaden, diversify and advance critical thinking pertaining to ethnic 'Other' females in sport and physical culture. The purpose of the collection is both to produce knowledge and privilege otherwise subjugated knowledges, which individually and collectively present counter-narratives that better speak to the lived realities of racially oppressed groups of women and girls. Race, Gender and Sport: The Politics of Ethnic 'Other' Girls and Women is important reading for all students and scholars with an interest in the sociology of sport, gender studies, or race and ethnicity studies.
Introduction : sport, race and gender : the politics of ethnic "other" girls and women / Aarti Ratna and Sumaya Farooq Samie -- Mapping the field : research about ethnic "other" females, sport and physical culture / Aarti Ratna and Sumaya Farooq Samie -- De/colonizing "sporting Muslim women" : post-colonial feminist reflections on the dominant portrayal of sporting Muslim women in academic research, public forums and mediated representations / Sumaya Farooq Samie -- Theoretical considerations in the examination of African American girls and women in sport / Akilah R. Carter-Francique -- Re-confronting whiteness : on-going challenges in sport and leisure research / Beccy Watson and Sheila Scraton -- "Using the pen as a weapon" : the resistance of an outsider within / Aarti Ratna -- Confronting the "whiteness" of women's cricket : excavating hidden truths and knowledge to make sense of non-white women's experiences of cricket / Raffaele Nicholson -- Ladies-only! : empowerment and comfort in gender-segregated kickboxing in the Netherlands / Jasmijn Rana -- Lorena "La Reina" Ochoa : disindentifying toward brown solidarity / Katherine Jamieson and Yeomi Choi -- Do women get the offside rule? : female fans, labelling and stereotypes in Turkey / Itir Erhart -- Sports coaching and the inclusion of Black women in the United Kingdom / Alexander J. Rankin-Wright and Leanne Norman.
Keywords: Sports for women -- Social aspects; Women athletes -- Social conditions; Racism in sports